Gut microbial profile is altered in primary biliary cholangitis and partially restored after UDCA therapy. Issue 3 (17th February 2017) - Tang, Ruqi; Wei, Yiran; Li, Yanmei; Chen, Weihua; Chen, Haoyan; Wang, Qixia; Yang, Fan; Miao, Qi; Xiao, Xiao; Zhang, Haiyan; Lian, Min; Jiang, Xiang; et al.
Abstract : Objective: A close relationship between gut microbiota and some chronic liver disorders has recently been described. Herein, we systematically performed a comparative analysis of the gut microbiome in primary biliary cholangitis (PBC) and healthy controls. Design: We first conducted a cross-sectional study of 60 ursodeoxycholic acid (UDCA) treatment-naïve patients with PBC and 80 matched healthy controls. Second, an independent cohort composed of 19 treatment-naïve patients and 34 controls was used to validate the results. Finally, a prospective study was performed in a subgroup of 37 patients with PBC who underwent analysis before and after 6 months of UDCA treatment. Faecal samples were collected, and microbiomes were analysed by 16S ribosomal RNA gene sequencing. Results: A significant reduction of within-individual microbial diversity was noted in PBC (p=0.03). A signature defined by decreased abundance of four genera and increased abundance of eight genera strongly correlated with PBC (area under curve=0.86, 0.84 in exploration and validation data, respectively). Notably, the abundance of six PBC-associated genera was reversed after 6 months of UDCA treatment. In particular, Faecalibacterium, enriched in controls, was further decreased in gp210-positive than gp210-negative patients (p=0.002). Of interest was the finding that the increased capacity for the inferred pathway, bacterial invasion of epithelial cells in PBC, highly correlated with the abundance of bacteria belonging to Enterobacteriaceae . Conclusions: This study presents a comprehensive landscape of gut microbiota in PBC. Dysbiosis was found in the gut microbiome in PBC and partially relieved by UDCA. Our study suggests that gut microbiota is a potential therapeutic target and diagnostic biomarker for PBC.